Effects of pan cooking on micropollutants in meat. (1st October 2017) - Planche, Christelle; Ratel, Jérémy; Blinet, Patrick; Mercier, Frédéric; Angénieux, Magaly; Chafey, Claude; Zinck, Julie; Marchond, Nathalie; Chevolleau, Sylvie; Marchand, Philippe; Dervilly-Pinel, Gaud; Guérin, Thierry; et al.
Highlights: GC×GC-TOF/MS successfully separated a mix of 189 PCBs, 17 PCDD/Fs and 16 pesticides. The most common cooking practice induced an average loss of 30% of PCBs. Cooking losses exceed 80% for some thermosensitive pesticides. No cooking effect was observed for PCDD/Fs and trace elements. Abstract: This work presents the effects of pan cooking on PCBs, PCDD/Fs, pesticides and trace elements in meat from a risk assessment perspective. Three different realistic cooking intensities were studied. A GC×GC-TOF/MS method was set up for the multiresidue analysis of 189 PCBs, 17 PCDD/Fs and 16 pesticides whereas Cd, As, Pb and Hg were assayed by ICP-MS. In terms of quantity, average PCB losses after cooking were 18 ± 5% for rare, 30 ± 3% for medium, and 48 ± 2% for well-done meat. In contrast, average PCDD/F losses were not significant. For pesticides, no loss occurred for aldrin, lindane, DDE or DDD, whereas losses exceeding 80% were found for dieldrin, sulfotep or phorate. Losses close to the margin of error were observed for trace elements. These results are discussed in light of the physicochemical properties of the micropollutants as well as of water and fat losses into cooking juice.